Phase Ib study of eltrombopag and azacitidine in patients with high‐risk myelodysplastic syndromes and related disorders (the ELASTIC study). (2nd August 2022) - Sternberg, Alexander; Boucher, Rebecca; Coulthard, Helen Chantal; Raghavan, Manoj; Culligan, Dominic; Jackson, Aimee; Cargo, Catherine; Dennis, Mike; Metzner, Marlen; O'Sullivan, Jennifer; Moore, Rachel; Bowen, David; et al.
Summary: Treating adverse risk myelodysplastic syndromes with azacitidine exacerbates thrombocytopenia. We report a study of eltrombopag in combination with azacitidine using a 3 + 3 cohort design. Patients with baseline platelets of <150 × 10 9 /l received eltrombopag ranging from 25 to 300 mg. An 8‐day pre‐phase of eltrombopag was followed by two cycles of combined therapy. Amongst 31 patients, there were no dose‐limiting toxicities. The maximum tolerated dose (MTD) was 300 mg. Transient increases in bone marrow blasts at day 8 were common but no patient had protocol‐defined progression following eltrombopag monotherapy. Marrow response rates after three and six treatment cycles were 32% and 29% respectively. In all, 70% of patients treated below and 36% treated at the MTD achieved a modified International Working Group 2006 platelet response at the end of cycle two. Of the platelet transfusion independent patients at baseline, 67% treated at the MTD became transfusion dependent during the first two cycles of treatment. Apart from lack of disease progression, our findings concur with a previously reported Phase III study (A StUdy of eltromboPag in myelodysPlastic SyndrOmes Receiving azaciTidine [SUPPORT]). We conclude that eltrombopag/azacitidine is safe in terms of conventional measures defined by adverse‐event reporting. However, in light of SUPPORT and our own descriptive findings regarding efficacy, further combination studies in high‐risk disease should be considered with caution.